Comparison between the Parliamentary and the Presidential System - Pulami Magar, Rudra Bahadur (Janaprakash Journal of Multidisciplinary Research, 2025)
This manuscript aims to present a comparative analysis between parliamentary and presidential systems of government, examining their structural features, functional structure, and impact on political stability, good governance, and democratic accountability. The main goal of the study is to identify the strengths and weaknesses of both systems in terms of executive-legislative relations, leadership stability, inclusiveness, and policy continuity. Methodologically, this research uses a qualitative comparative method, using constitutional provisions, scholarly literature, and secondary data from selected countries that have adopted parliamentary and presidential systems. It concludes that while parliamentary systems promote accountability and inclusiveness through collective executive responsibility, coalition politics can lead to government instability. In contrast, presidential systems provide fixed tenure and policy stability, but they can also lead to problems such as centralization of power and weak oversight by the legislature. The study’s findings show that no system is universally superior, but its effectiveness depends on historical background, political culture, judicial system, and institutional maturity. As a consequence, it seems necessary to prioritize contextual suitability, balanced power-sharing, and democratic security in constitution-making and governance reform, especially for multi-party and multicultural societies like Nepal.